(untitled) (Fiep Bulletin - online, 2015)
This study presents the perception that women who practice aerobics have in relation to the changes caused by the aging process. We used a sample of 11 women aged between 30 and 60 years old because they are in transition from adulthood to aging, we applied an interview with some questions and noted the major changes that lead people to perceive aging. In the results, major changes in individuals that lead them to perceive aging were identified; among them we noticed that most understand that aging is a natural process of body change.